Cholestasis: The ABCs of Cellular Mechanisms for Impaired Bile Secretion – Transporters and Genes - Eldon A Shaffer (Canadian Journal of Gastroenterology)
The transport of bile salts, organic anions and cations, bilirubin and other substances from the portal blood into the biliary system is accomplished through the action of an array of transporter proteins in the hepatocyte. Transporters on the basolateral membrane, which faces the space of Disse, are responsible for the uptake of bile salts and organic anions. Once translocated through the hepatocyte to the canalicular membrane, other ATP pumps provide the energy to export bile salts, phospholipids and organic ions into the bile. Canalicular transport is rate limiting. Defects in specific canalicular transporters are responsible for many of the intrahepatic cholestatic syndromes that occur in children and adults. Moreover, cholestasis provokes changes in several transport mechanisms, many of which appear to be compensatory and serve to protect the liver from the toxic effects of accumulated materials. The identification and characterization of the major transporters responsible for bile formation have yielded a more precise classification of the cholestatic syndromes of infancy and childhood, and are unlocking the molecular mechanism of acquired cholestasis in adults. This review identifies the basic physiology of bile production and the actions of the key transporters, indicates the clinical relevance and possible treatments of transport disorders, and provides an illustrative case.